Diagnostic efficiency of glycosylated hemoglobin test in comparison to oral glucose tolerance test: a data mining study - Serteser, M.; Durer, Z. A.; Serdar, M. A.; Erdemgil, Y.; Aksungar, F.; Coskun, A.; Unsal, I.; Ozpinar, A. (WILEY-BLACKWELL, 2016)
41st FEBS Congress on Molecular and Systems Biology for a Better Life, Kusadasi, TURKEY, SEP 03-08, 2016